O contrassenso do "empregado hipersuficiente" em uma relação jurídica ainda assimétrica - Ferreira, Sergio Murillo Bocardo [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The sole paragraph of CLT’s article 444, introduced by Law 13.467/17, has established the possibility that a portion of the employees be able to negotiate contractual clauses directly with their employers with reduced legal restrictions to be observed. This represents a relativism of the principle of protection and, besides raising allegations of unconstitutionality, it generates fierce doctrinal debates for impacting guiding concepts of the Labour Law. This research attempts to understand the notion of employee hypossufficiency in this branch of law, as well as to understand pressures to reduce the protection offered to employees in labor legislation, in order to investigate the adequacy of admitting a “hypersufficient employee” within the Brazilian legal system. This work was developed with a qualitative approach, through the use of a bibliographic research, considering the specialized literature regarding the subject. Among other things, the research reveals that the aforementioned legal innovation is often criticized for contradicting premises of Labour Law and employment relationship itself, besides the existing criticism regarding the legal requirements used to consider an employee fit for a different framework.

O parágrafo único do art. 444 da CLT, introduzido pela Lei 13.467/17, estabeleceu a possibilidade de que uma fração dos empregados negocie cláusulas contratuais diretamente com o empregador com menor número de restrições legais a serem observadas. Tal novidade representa uma relativização do princípio da proteção e, afora as alegações de inconstitucionalidades, gera intenso debate doutrinário por impactar conceitos norteadores do Direito do Trabalho. Assim, a presente pesquisa busca compreender a noção de hipossuficiência do empregado neste ramo do direito, assim como as pressões para reduzir a proteção garantida aos obreiros na legislação trabalhista, de modo a averiguar a pertinência de se admitir a figura do chamado “empregado hipersuficiente” no ordenamento jurídico pátrio. Opta-se por uma abordagem qualitativa, por meio de uma revisão bibliográfica da literatura especializada sobre o tema. Entre outras coisas, a pesquisa revela que a inovação legislativa em comento recebe críticas por contrariar pressupostos da seara trabalhista e da própria relação de emprego, além de haver questionamentos acerca dos critérios definidos pelo legislador para o enquadramento diferenciado do empregado.
The contradiction of a "hypersufficient employee" in a still asymmetric legal relationship
Keywords: hypersufficient employee; Labour law; Labour law reform.; Empregado hipersuficiente; Direito do Trabalho; Reforma trabalhista.